A spoonful of sugar: human exposure to microplastics through consumption of processed sugarcane - Jamila Patterson; K. Immaculate Jeyasanta; M. Narmatha Sathish; Andy M. Booth; V. Glen Esmeralda; R. L. Laju (Food Additives & Contaminants: Part A, 2026)

Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Acorn woodpeckers alter resource use, group size, and spring productivity across an urban landscape - Olivia R. Knapp; Kendra E. Forster; Alexander J. Rurik; Isabelle Hugoniot; Eric S. Reyes; Peter B. Schramm; Corban A. Muthiah; Aaron Wong; Seth C. Wilmoth; Sophia L. McRae; Caleb Courson; Theodore J. Patterson; et al. (Urban Ecosystems, 2026)
Access to suitable resources shapes the evolution and maintenance of avian cooperative breeding by influencing whether an individual will have a greater chance of survival and reproduction by dispersing or remaining on a natal territory. Cooperatively-breeding species exhibit altered dispersal according to food availability and habitat quality, but the relationship between resource use, group size, and reproduction in human-altered landscapes remains to be studied. We examined how urbanization, key resource availability, and resource use relate to differences in group size and number of offspring in an urban population of facultative cooperatively-breeding acorn woodpeckers. Acorn woodpeckers shifted to increased use of ornamental trees, palms, and anthropogenic structures for granaries in more urbanized areas and where oak trees, a key historic food and granary resource, are in lower abundance and proximity. Pair breeding was more prevalent in urbanized areas and seemed to be primarily associated with use of utility poles for granaries. In general, territories with utility poles as granaries and higher urbanization levels hosted smaller group sizes. In contrast, while the number of fledglings was higher in larger groups, it did not vary with urban resources when controlling for group size. Our findings suggest that land conversion levels and the relative availability of historic and novel resources shape habitat quality, resulting in differing patterns of group living and subsequent productivity across the urban landscape. This indicates that while novel resources may enable wildlife to occupy urban areas, they may also influence the social behavior of facultative cooperative breeders.

United States stakeholder insights on genetic testing for equine health and breeding - Michael J. Mienaltowski; Sarah Hernandez; Emma Nastrini; Carissa L. Wickens; Molly E. McCue; Laura Patterson Rosa; Elaine M. Norton; Annette M. McCoy; Samantha A. Brooks (Journal of Equine Veterinary Science, 2026)

Post-release mortality of red snapper, Lutjanus campechanus, in US Atlantic waters off northeast Florida estimated with three-dimensional acoustic telemetry - Selia Zimmermann; Liam Kehoe; Miaya Taylor; Joseph H. Tarnecki; Nathan M. Bacheler; Zachary A. Siders; William F. Patterson III (Fisheries Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

Net erosion and accretion of experimental blocks of Porites sp. skeleton deployed for 10.6 to 20.3 years at Lizard Island, northern Great Barrier Reef - Madhavi A. Patterson; Jody M. Webster; Veronique Chazottes; Willem Renema; Zsanett Szilagyi; Pat Hutchings (Coral Reefs, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Impact of flooding events on microplastic distribution from rivers to coastal areas: a case study from Tuticorin, Southeast India - Jamila Patterson; K. Immaculate Jeyasanta; M. Narmatha Sathish; Andy M. Booth; R.L. Laju; V. Glen Emeralda; Bakan Jagdish Sudhakar (Marine Pollution Bulletin, 2025)

Corrigendum to “impact of flooding events on microplastic distribution from rivers to coastal areas: A case study from Tuticorin, Southeast India” [Mar. Pollut. Bull. (221) 118471] - Jamila Patterson; K. Immaculate Jeyasanta; M. Narmatha Sathish; Andy M. Booth; R.L. Laju; V. Glen Emeralda; Bakan Jagdish Sudhakar (Marine Pollution Bulletin, 2025)

The ecotoxicological implications and contamination profile of organochlorine pesticides (OCPs), organophosphorus pesticides (OPPs), and heavy metals, in Tuticorin, Southeast coast of India - M. Narmatha Sathish; Jamila Patterson (Regional Studies in Marine Science, 2025)

Edible Campus: Empowering Students Through Integrated Campus Gardening and Meal Preparation Programs - J. Lefaver; C. Starr; D. Folliard; B. Flower; J. Patterson; M. Duffrin (Journal of the Academy of Nutrition and Dietetics, 2025)

Habitat selection as a reduction in habitat variance - Jenna Knight; James A. Schaefer; Brent R. Patterson; Stephen Sucharzewski; Joseph M. Northrup (Acta Oecologica, 2025)

Satellite tracking reveals sex-specific differences in the geographical and vertical habitat use of Whale sharks, Rhincodon typus, in the Eastern Indian ocean - Colby J. Bignell; Toby A. Patterson; Anthea Donovan; Mathew A. Vanderklift; Wayne Rochester; Jayson M. Semmens; Richard D. Pillans (Marine Biology, 2025)
Satellite tagging of whale sharks ( Rhincodon typus) has typically focused on juvenile males which dominate coastal aggregation sites, with limited data on the movements of females. We satellite-tagged 39 whale sharks of 3.75–9.27 m total length at Ningaloo reef between 2015 and 2018 with a roughly equivalent sex ratio (Male = 20, Female = 18, Unknown = 1).We aimed to identify differences in horizontal and vertical movements between the sexes using state-space models, kernel utilisation distributions (KUDs) and generalised additive models (GAMs). Deployment spans ranged from 9 to 340 days (mean = 132.4 ± SE = 17.9 days, N = 35) and 22 tracks exceeded 1000 km in length (mean = 2557 ± SE = 370 km, N = 35). Whale sharks spent > 90% of time in epipelagic waters ≤ 200 m and dived to a maximum depth of 1906 m. Sex-specific differences in horizontal and vertical movements were related to distinct temperature preferences. Females spent more time in offshore waters and preferred cooler Sea Surface Temperatures (SST) than males. Female movements were strongly influenced by increasing SSTs with greater space and depth use, while the space and depth use of males was more consistent with SSTs < 28 °C. We found no relationships between whale shark size and their space, depth or temperature use, though most individuals were immature (< 8 m, N = 24). The results provide novel evidence of sex-specific horizontal and vertical movements over broad geographical scales, extending current knowledge on the movement ecology and sex-specific demography of this endangered species.

Spatiotemporal drivers of water quality and phytoplankton communities in a cyanobacteria-dominated reservoir provide management insights - Linnea A. Rock; William W. Fetzer; Lindsay S. Patterson; Samuel J. Sillen; Ron Steg; Annika W. Walters; Sarah M. Collins (Environmental Monitoring and Assessment, 2025)
Reservoirs serve critical roles providing drinking water, irrigation, flood control, hydropower, recreation, fisheries, and aquatic habitat. Yet their physical position, complex shape, and large watersheds make reservoirs especially susceptible to eutrophication and harmful algal bloom (HAB) production. Boysen Reservoir, WY, is a high priority for proactive nutrient management because it is an important source for drinking water and recreation, and has a history of toxic cyanobacterial blooms. We combined four years of comprehensive monitoring efforts by state and federal agencies to characterize the spatiotemporal patterns of nutrient inflow, internal water quality dynamics, and phytoplankton community shifts in Boysen Reservoir. We found nutrient inflow was hydrologically driven, with snowmelt runoff transporting high nutrient loads. Our findings suggest physicochemical and nutrient conditions of the reservoir were strongly different between the furthest reaches of the reservoir, but less variable among the intermediate sites. Space did not play a role in phytoplankton community dynamics, but time was an important factor. Cyanobacteria dominated phytoplankton communities by mid-summer across the reservoir and were driven mainly by temporal physicochemical conditions, like stratification and water temperature. The two most dominant phytoplankton taxa across the four years of sampling were N-fixing, toxin producing cyanobacteria. Extensive monitoring efforts and data analyses can illuminate strategies to safeguard water resources via understanding the drivers of water quality changes and HAB production.

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

Call for neurofibromatosis specialty care clinics in South Carolina - Camerun C. Washington; Kenya M. De Leon; Jessica A. Cooley Coleman; Wesley G. Patterson; Michael J. Lyons (Journal of Community Genetics, 2025)

4-H youth comprehension, perceptions, and selection of tack and its implications for equine welfare - K. Irvine; C.L. Wickens; M. Nelson; R. Prasad; L.N.R. Patterson (Journal of Equine Veterinary Science, 2025)

The effect of local perennial plants on the occurrence and traits of the Brachypodium distachyon complex along an aridity gradient - Megan K. Korte; Antonio J. Manzaneda; Luisa M. Martinez; Tamatha A. Patterson; Rampal S. Etienne; Louis van de Zande; Christian Smit (Plant Ecology, 2025)
Plant-plant interactions are well-known drivers of plant community dynamics and plant traits. Less well known is to what extent these interactions and their effects change along stress gradients. To study this, we assessed the local spatial association of the annual grass species Brachypodium hybridum and Brachypodium distachyon to perennial plants in ten sites along an aridity gradient in southeastern Spain and compared ten phenotypic traits of Brachypodium occurring underneath and outside the perennial plant canopy. We found that Brachypodium was less associated with perennials with increasing aridity but with a significant site effect. This site effect seemed to be due to one particular site, the removal of which from our analysis resulted in an even stronger negative correlation and uncovered a significant influence of the perennial plant. We also found that while overall three phenotypic traits (plant height, spike length, and seed number) were different between plants underneath perennial plants and plants outside perennials, only one of these differences (spike length) changed significantly along the gradient. Further, in controlled conditions, we found that the offspring of annual plants collected from outside perennial plant canopies in the least arid site flowered more rapidly than those from underneath perennial plants, but this difference was not observed for the most arid site. These results indicate that in patchy arid landscapes dominated by perennial plants, Brachypodium ’s response to the microhabitat provided by neighboring perennial plants changes along the aridity gradient, but other factors such as site and perennial plant may counteract or strengthen the effects of aridity.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Assessment of beach litter, including Abandoned, Lost, or Discarded Fishing Gear (ALDFG), along the coast of Tamil Nadu, India: Magnitude, sources, composition, pollution status, and management strategies - J.K. Patterson Edward; M. Jayanthi; Haraldur A. Einarsson; R. Kannan; R.L. Laju; K. Immaculate Jeyasanta; Narmatha Sathish; Jamila Patterson (Marine Pollution Bulletin, 2025)

The Relationship Between Diet Quality and 21-Year Cumulative Health Care Costs Among Australian Women: A Longitudinal Cohort Study - Erin D. Clarke; Jennifer N. Cartwright; Lee M. Ashton; Tracy L. Burrows; Alexis Hure; Deborah Loxton; Amanda J. Patterson; Clare E. Collins (Journal of the Academy of Nutrition and Dietetics, 2025)

Ontogenetic change in body shape for white sharks, Carcharodon carcharias , in Australian waters - Emily Hunt; Russell W. Bradford; David J. Booth; Cameron Doak; Toby A. Patterson; Victor M. Peddemors (Journal of Fish Biology, 2025)
The analysis of how biological shape changes across ontogeny can provide us with valuable information on how species adapt behaviorally, physiologically, and ecologically. The white shark Carcharodon carcharias is one of the largest and most widely distributed apex predators globally, yet an understanding of ontogenetic changes in body shape and relative scaling of length and weight measures is limited, especially in relation to foraging ecology. Through analysis of a suite of shape‐related metrics, we identified ontogenetic patterns of scaling throughout development. Isometric growth was exhibited for most metrics, failing to show a significant deviation from an isometric slope of 1.0 for length–length relationships, and 3.0 for weight–length relationships. The most notable difference from this trend was the negative allometric growth observed for the upper caudal‐fin lobe length, trunk length, and the mouth length. The surface area of the fins also presented a strong, positive relationship with precaudal length (PCL) and the girth at the pectoral fin. Negative allometric growth was exhibited for three of the fins (pectoral, upper caudal fin, and lower caudal fin) against PCL, exhibiting a significant deviation from the expected isometric growth of 2.0 for area–length relationships. There were no significant differences in morphometric relationships between geographic regions within Australia that samples were collected from. No differences between the sexes were identified; however, this may be an artifact of the lack of mature animal samples. Conversely, life stage was found to have a significant effect on the girth–length and weight–length relationships. The development of regression equations for morphometric measures allows the assessment of white shark body condition and may serve as an assessment tool to understand the potential impacts of human‐induced environmental change on white sharks.

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

The effects of vessel speed and size on the lethality of strikes of large whales in U.S. waters - Lance P. Garrison; Niki E. Lisi; Meghan Gahm; Eric M. Patterson; Hannah Blondin; Caroline P. Good (Frontiers in Marine Science, 2025)
Vessel strikes are a substantial source of mortality for large whales worldwide and may pose conservation threats for small populations. Model-based estimates of mortality rates, which inform management strategies to reduce vessel strike mortality, typically assume a reduced likelihood that a whale-vessel collision will be lethal to the whale at slower vessel speeds. In this study, we reviewed and updated available data on observed whale-vessel interactions in U.S. waters and developed a new model characterizing the probability that an interaction will be lethal to the whale as a function of vessel speed, length (as a proxy for mass), and whale taxon. We found a significant effect of vessel size class on the probability of lethality. In addition, decreasing vessel speeds reduced the likelihood of a lethal outcome for all vessel size classes, but this effect was strongest for vessels less than 108m in length. The probability that a strike by a very large ocean-going vessel will be lethal exceeded 0.80 at all speeds above 5 knots. Whale taxon also affected both the likelihood of a lethal strike and the effect of vessel speed. Humpback whales ( Megaptera novaeangliae ) had significantly lower rates of lethal strikes compared to other large whales. This difference may be associated with data limitations, differing behavioral responses between species, varying vessel types between regions or differences in body composition and blubber thickness. The model is consistent with biophysical models that demonstrate a high rate of strike lethality for large vessels with high masses. Vessel speed restrictions are one of the primary approaches to reduce the risk of vessel strikes to whales in the face of continued industrialization of the oceans, and the model presented here will help better inform management efforts.

Spatiotemporal dynamics and habitat use of red snapper (Lutjanus campechanus) on the southeastern United States Atlantic continental shelf - Nathan M. Bacheler; William F. Patterson III; Joseph H. Tarnecki; Kyle W. Shertzer; Jeffrey A. Buckel; Nathan J. Hostetter; Krishna Pacifici; Viviane Zulian; Walter J. Bubley (Fisheries Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The biodiversity of ice‐free Antarctica database - Aleks Terauds; Jasmine R. Lee; Hannah S. Wauchope; Ben Raymond; Dana M. Bergstrom; Peter Convey; Claire Mason; Charlotte R. Patterson; Sharon A. Robinson; Anton Van de Putte; David Watts; Steven L. Chown (Ecology, 2025)
Antarctica is one of Earth's most untouched, inhospitable, and poorly known regions. Although knowledge of its biodiversity has increased over recent decades, a diverse, wide‐ranging, and spatially explicit compilation of the biodiversity that inhabits Antarctica's permanently ice‐free areas is unavailable. This absence hinders both Antarctic biodiversity research and the integration of Antarctica in global biodiversity–related studies. Fundamental and applied research on biodiversity patterns, ecological structure and function, and options for conservation are reliant on spatially resolved, taxonomically consistent observations. Such information is especially important for modern, data‐driven biodiversity science, in both Antarctica and globally, and forms the backbone of biodiversity informatics, reflected, for example, in the Darwin Core Standard used by the Global Biodiversity Information Facility. Biodiversity data are also essential to fulfill the conservation requirements for Antarctica, as set out in the Protocol on Environmental Protection to the Antarctic Treaty and inform the design of systematic surveys to address biodiversity and ecological knowledge gaps, for both specific taxa and ecosystems. Such surveys are key requirements for understanding and mitigating the impacts of environmental change on the region's biodiversity. Here, we address these requirements through the public release of The Biodiversity of Ice‐free Antarctica Database. In 2008, we extracted a subset of biodiversity records only from terrestrial ice‐free areas from the Scientific Committee on Antarctic Research (SCAR) Antarctic Biodiversity Database. We have subsequently added thousands of records from a range of sources: checking, and where necessary (and possible), correcting the spatial location, clarifying, cross‐referencing, and harmonizing taxonomy with globally recognized sources, and documenting the original source of records. The Biodiversity of Ice‐free Antarctica Database spans the early 1800s to 2019 (with most records collected after 1950) and represents the most comprehensive consolidation of Antarctic ice‐free biodiversity occurrence data yet compiled into a single database. The Biodiversity of Ice‐free Antarctica Database contains 35,654 records of 1890 species in over 800 genera across six kingdoms and spans all Antarctic Conservation Biogeographic Regions. These data are released under a CC BY Attribution License ( http://creativecommons.org/licenses/by/4.0/ ).

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Organic matter is a predominant control on total mercury concentration of near-surface lake sediments across a boreal to low Arctic tundra transect in northern Canada - Jennifer M. Galloway; Michael B. Parsons; Omid H. Ardakani; Hendrik Falck; Richard E. Fewster; Graeme T. Swindles; Hamed Sanei; Michael J. Palmer; Nawaf A. Nasser; R. Timothy Patterson (Science of The Total Environment, 2024)

Salt in foods: a definitive source of microplastics to humans - Jamila Patterson; K. Radampola; P. B. Terney Pradeep Kumara; Glen Esmeralda; K. Immaculate Jeyasanta; M. Narmatha Sathish (Journal of Consumer Protection and Food Safety, 2024)

Immune gene regulation is associated with age and environmental adversity in a nonhuman primate - Marina M. Watowich; Christina E. Costa; Kenneth L. Chiou; Elisabeth A. Goldman; Rachel M. Petersen; Sam Patterson; Melween I. Martínez; Kirstin N. Sterner; Julie E. Horvath; Michael J. Montague; Michael L. Platt; Lauren J. N. Brent; et al. (Molecular Ecology, 2024)
Phenotypic aging is ubiquitous across mammalian species, suggesting shared underlying mechanisms of aging. Aging is linked to molecular changes to DNA methylation and gene expression, and environmental factors, such as severe external challenges or adversities, can moderate these age‐related changes. Yet, it remains unclear whether environmental adversities affect gene regulation via the same molecular pathways as chronological, or ‘primary’, aging. Investigating molecular aging in naturalistic animal populations can fill this gap by providing insight into shared molecular mechanisms of aging and the effects of a greater diversity of environmental adversities – particularly those that can be challenging to study in humans or laboratory organisms. Here, we characterised molecular aging – specifically, CpG methylation – in a sample of free‐ranging rhesus macaques living off the coast of Puerto Rico ( n samples = 571, n individuals = 499), which endured a major hurricane during our study. Age was associated with methylation at 78,661 sites (31% of all sites tested). Age‐associated hypermethylation occurred more frequently in areas of active gene regulation, while hypomethylation was enriched in regions that show less activity in immune cells, suggesting these regions may become de‐repressed in older individuals. Age‐associated hypomethylation also co‐occurred with increased chromatin accessibility while hypermethylation showed the opposite trend, hinting at a coordinated, multi‐level loss of epigenetic stability during aging. We detected 32,048 CpG sites significantly associated with exposure to a hurricane, and these sites overlapped age‐associated sites, most strongly in regulatory regions and most weakly in quiescent regions. Together, our results suggest that environmental adversity may contribute to aging‐related molecular phenotypes in regions of active gene transcription, but that primary aging has specific signatures in non‐regulatory regions.

Molecular features of uranium-binding natural organic matter in a riparian wetland determined by ultrahigh resolution mass spectrometry - Chen Xu; Aleksandar I. Goranov; Daniel I. Kaplan; Peng Lin; Chris M. Yeager; Nicole Patterson; Helen Jiang; Patrick G. Hatcher; Peter H. Santschi (Science of The Total Environment, 2024)

Cultivating Care: A Workshop to Identify and Support Students with Disordered Eating Patterns - G. Molina; J. Patterson; M. Duffrin; T. Miralaeff; K. Lockwood (Journal of the Academy of Nutrition and Dietetics, 2024)

Microplastics contamination in commercial fish meal and feed: a major concern in the cultured organisms - Immaculate Jeyasanta; M. Narmatha Sathish; Jamila Patterson; V. Glen Esmeralda; Laju R.L (Chemosphere, 2024)

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Temporal dynamics in gray wolf space use suggest stabilizing range in the Great Lakes region, USA - M. van den Bosch; D.E. Beyer; J.D. Erb; M.G. Gantchoff; K.F. Kellner; D.M. MacFarland; B.R. Patterson; J.L. Price Tack; B.J. Roell; J.L. Belant (Biological Conservation, 2024)

Factors influencing cyanobacteria blooms: review of the historical monitoring data to assess management options for Lake Horowhenua - Max M. Gibbs; Jon Roygard; Maree Patterson; Logan Brown; David Brown (New Zealand Journal of Marine and Freshwater Research, 2024)
Factors influencing cyanobacterial blooms in Lake Horowhenua, Aotearoa/New Zealand, have been deduced from over 40 yrs routine monitoring data, detailed studies and high frequency (15‐min interval) data from an in‐lake monitoring buoy. Lake Horowhenua is currently hypertrophic but flips between a winter clear‐water, macrophyte dominated phase ( Potamogeton crispus), and a turbid phytoplankton dominated phase with substantial cyanobacterial ( Microcystis sp. ) blooms from mid‐summer to autumn. Nitrogen for growth comes from agriculture and horticulture via groundwater and spring‐fed streams. Phosphorus is released from the sediment when the weed beds die back. These nutrients stimulate the growth of Microcystis sp. , until the water temperature falls below 15°C. Microcystis sp can raise the pH to over 10, which releases P from the sediment, sustaining its growth. High pH transforms non‐toxic ammonium‐N released from the sediment to toxic unionised NH 3 , which may contribute to fish kills in summer/autumn. Management strategies cannot use P‐inactivation agents for cultural reasons and eradicating the macrophyte beds by spraying would cause the lake to permanently flip to a turbid state. Management of the macrophyte beds with a weed harvester is being trialled to allow a gradual replacement of P. crispus with indigenous species from the seed bank in the sediment.

Ruminating on soil carbon: Applying current understanding to inform grazing management - Paige L. Stanley; Chris Wilson; Erica Patterson; Megan B. Machmuller; M. Francesca Cotrufo (Global Change Biology, 2024)
Among options for atmospheric CO 2 removal, sequestering soil organic carbon (SOC) via improved grazing management is a rare opportunity because it is scalable across millions of globally grazed acres, low cost, and has high technical potential. Decades of scientific research on grazing and SOC has failed to form a cohesive understanding of how grazing management affects SOC stocks and their distribution between particulate (POM) and mineral‐associated organic matter (MAOM)—characterized by different formation and stabilization pathways—across different climatic contexts. As we increasingly look to grazing management for SOC sequestration on grazinglands to bolster our climate change mitigation efforts, we need a clear and collective understanding of grazing management's impact on pathways of SOC change to inform on‐the‐ground management decisions. We set out to review the effects of grazing management on SOC through a unified plant ecophysiology and soil biogeochemistry conceptual framework, where elements such as productivity, input quality, soil mineral capacity, and climate variables such as aridity co‐govern SOC accumulation and distribution into POM and MAOM. To maximize applicability to grazingland managers, we discuss how common management levers that drive overall grazing pattern, including timing, intensity, duration, and frequency can be used to optimize mechanistic pathways of SOC sequestration. We discuss important research needs and measurement challenges, and highlight how our conceptual framework can inform more robust research with greater applicability for maximizing the use of grazing management to sequester SOC.

Estimating reductions in the risk of vessels striking whales achieved by management strategies - Jessica V. Redfern; Brooke C. Hodge; Daniel E. Pendleton; Amy R. Knowlton; Jeffrey Adams; Eric M. Patterson; Caroline P. Good; Jason J. Roberts (Biological Conservation, 2024)

Quantifying conditions required for varve formation in meromictic Crawford Lake, Ontario, Canada: important process for delimiting the Anthropocene epoch - Brendan M. Llew-Williams; Francine M. G. McCarthy; Andrea M. Krueger; Nicholas L. Riddick; Michael D. MacKinnon; Krysten M. Lafond; R. Timothy Patterson; Nawaf A. Nasser; Martin J. Head; Michael F. J. Pisaric; Kevin W. Turner; Joseph I. Boyce; et al. (Journal of Paleolimnology, 2024)

Direct injection liquid chromatography-tandem mass spectrometry as a sensitive and high-throughput method for the quantitative surveillance of antimicrobials in wastewater - Jinglong Li; Katja M. Shimko; Chang He; Brad Patterson; Richard Bade; Ryan Shiels; Jochen F. Mueller; Kevin V. Thomas; Jake W. O'Brien (Science of The Total Environment, 2023)

Ultraconserved elements resolve phylogenetic relationships and biogeographic history of African-Malagasy bent-winged bats (Miniopterus) - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Holly L. Lutz; Bernard R. Agwanda; Natalia Cortés-Delgado; Stefania Briones; Richard H. Ree; Bruce D. Patterson (Molecular Phylogenetics and Evolution, 2023)

Correction to: Changing Biogeochemistry and Invertebrate Community Composition at Newly Deployed Artificial Reefs in the Northeast Gulf of Mexico - Kendra K. Babcock; Florian Cesbron; William F. Patterson; Steven B. Garner; Lisa A. Waidner; Jane M. Caffrey (Estuaries and Coasts, 2023)

Microplastic contamination in Indian rural and urban lacustrine ecosystems - R.L. Laju; M. Jayanthi; K. Immaculate Jeyasanta; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Comparative study on the status of microplastics in different functional areas of Tuticorin, Southeast coast of India - M. Narmatha Sathish; Jamila Patterson (Science of The Total Environment, 2023)

Caspase 5 depletion is linked to hyper-inflammatory response and progeroid syndrome - Fuki M. Hisama; Renuka Kandhaya Pillai; Julia Sidorova; Karynne Patterson; Carolina Gokingco; Michal Yacobi-Bach; Junko Oshima (GeroScience, 2023)
A progeroid family was found to harbor a pathogenic variant in the CASP5 gene that encodes inflammatory caspase 5. Caspase 5-depleted fibroblasts exhibited hyper-activation of inflammatory cytokines in response to pro-inflammatory stimuli. Long-term intermittent hyper-inflammatory response is likely the cause of the accelerated aging phenotype comprised of earlier onset of common aging diseases, supporting inflammaging as a potential common disease mechanism of progeroid syndromes and possibly normative aging.

Evaluation of Zoetis GeneMax Advantage genomic predictions in commercial Bos taurus Angus cattle - Brian.C. Arisman; Troy N. Rowan; Jordan M. Thomas; Harly J. Durbin; William R. Lamberson; David J. Patterson; Jared E. Decker (Livestock Science, 2023)

Seasonal and spatial variations in the distribution pattern, sources and impacts of microplastics along different coastal zones of Tamil Nadu, India - K. Immaculate Jeyasanta; M. Jayanthi; R.L. Laju; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Marine Pollution Bulletin, 2023)

Forecast‐ready models to support fisheries' adaptation to global variability and change - Kylie L. Scales; Thomas S. Moore; Bernadette Sloyan; Claire M. Spillman; J. Paige Eveson; Toby A. Patterson; Ashley J. Williams; Alistair J. Hobday; Jason R. Hartog (Fisheries Oceanography, 2023)
Ocean and climate drivers affect the distribution and abundance of marine life on a global scale. Marine ecological forecasting seeks to predict how living marine resources respond to physical variability and change, enabling proactive decision‐making to support climate adaptation. However, the skill of ecological forecasts is constrained by the skill of underlying models of both ocean state and species‐environment relationships. As a test of the skill of data‐driven forecasts for fisheries, we developed predictive models of catch‐per‐unit‐effort (CPUE) of tuna and billfish across the south‐west Pacific Ocean, using a 12‐year time series of catch data and a large ensemble climate reanalysis. Descriptors of water column structure, particularly temperature at depth and upper ocean heat content, emerged as useful predictors of CPUE across species. Enhancing forecast skill over sub‐seasonal to multi‐year timescales in any system is likely to require the inclusion of sub‐surface ocean data and explicit consideration of regional physical dynamics.

Offshore decommissioning horizon scan: Research priorities to support decision-making activities for oil and gas infrastructure - Sarah M. Watson; Dianne L. McLean; Brian J. Balcom; Silvana N.R. Birchenough; Alison M. Brand; Elodie C.M. Camprasse; Jeremy T. Claisse; Joop W.P. Coolen; Tom Cresswell; Bert Fokkema; Susan Gourvenec; Lea-Anne Henry; et al. (Science of The Total Environment, 2023)

High-resolution entry and exit surface dosimetry in a 1.5 T MR-linac - E. Patterson; P. Stokes; D. Cutajar; A. Rosenfeld; J. Baines; P. Metcalfe; M. Powers (Physical and Engineering Sciences in Medicine, 2023)
The magnetic field of a transverse MR-linac alters electron trajectories as the photon beam transits through materials, causing lower doses at flat entry surfaces and increased doses at flat beam-exiting surfaces. This study investigated the response of a MOSFET detector, known as the MO Skin ™, for high-resolution surface and near-surface percentage depth dose measurements on an Elekta Unity. Simulations with Geant4 and the Monaco treatment planning system (TPS), and EBT-3 film measurements, were also performed for comparison. Measured MO Skin ™ entry surface doses, relative to D max , were (9.9 ± 0.2)%, (10.1 ± 0.3)%, (11.3 ± 0.6)%, (12.9 ± 1.0)%, and (13.4 ± 1.0)% for 1 × 1 cm 2 , 3 × 3 cm 2 , 5 × 5 cm 2 , 10 × 10 cm 2 , and 22 × 22 cm 2 fields, respectively. For the investigated fields, the maximum percent differences of Geant4, TPS, and film doses extrapolated and interpolated to a depth suitable for skin dose assessment at the beam entry, relative to MO Skin ™ measurements at an equivalent depth were 1.0%, 2.8%, and 14.3%, respectively, and at a WED of 199.67 mm at the beam exit, 3.2%, 3.7% and 5.7%, respectively. The largest measured increase in exit dose, due to the electron return effect, was 15.4% for the 10 × 10 cm 2 field size using the MO Skin ™ and 17.9% for the 22 × 22 cm 2 field size, using Geant4 calculations. The results presented in the study validate the suitability of the MO Skin ™ detector for transverse MR-linac surface dosimetry.

Decoupled Patterns of Diversity and Disparity Characterize an Ecologically Specialized Lineage of Neotropical Cricetids - Rafaela V. Missagia; Daniel M. Casali; Bruce D. Patterson; Fernando A. Perini (Evolutionary Biology, 2023)

Targeted metabolomics reveals plasma biomarkers and metabolic alterations of the aging process in healthy young and older adults - Paniz Jasbi; Janko Nikolich-Žugich; Jeffrey Patterson; Kenneth S. Knox; Yan Jin; George M. Weinstock; Patricia Smith; Homer L. Twigg; Haiwei Gu (GeroScience, 2023)

A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas - Ashley T. Simkins; Alison E. Beresford; Graeme M. Buchanan; Olivia Crowe; Wendy Elliott; Pablo Izquierdo; David J. Patterson; Stuart H.M. Butchart (Biological Conservation, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

The bioeconomic paradox of market-based invasive species harvest: a case study of the commercial lionfish fishery - Holden E. Harris; William F. Patterson; Robert N. M. Ahrens; Micheal S. Allen; David D. Chagaris; Sherry L. Larkin (Biological Invasions, 2023)

Advancing textural heterogeneity: Effect of manipulating multi-component model foods on the perception of textural complexity - Niamh M. Patterson; Yvonne S. Kuiper; Sophia A. Rodrigues; Bryony J. James; Nicholas Gant; Michael J. Hautus (Food Research International, 2023)

Microplastic pollution and its implicated risks in the estuarine environment of Tamil Nadu, India - K. Immaculate Jeyasanta; R.L. Laju; Jamila Patterson; M. Jayanthi; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Hydrochemical quality and microplastic levels of the groundwaters of Tuticorin, southeast coast of India - Jamila Patterson; R. L. Laju; K. Immaculate Jeyasanta; S. Shelciya; V. Glen Esmeralda; N. Gladwin Gnana Asir; M. Narmatha; Andy M. Booth (Hydrogeology Journal, 2023)

Age-dependent and modality-specific changes in the phenotypic markers Nav1.8, ASIC3, P2X3 and TRPM8 in male rat primary sensory neurons during healthy aging - Diego N. Messina; Emanuel D. Peralta; Alicia M. Seltzer; Sean I. Patterson; Cristian G. Acosta (Biogerontology, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Estimating Adult Pacific Salmon Energy Use in Coastal British Columbia and the Fraser River Estuary with Acoustic Accelerometer Transmitters - S. M. Wilson; S. G. Hinch; D. A. Patterson; E. J. Eliason; S. J. Cooke (Estuaries and Coasts, 2022)

Warfarin Overdose in an Adolescent Not Dependent on Anticoagulation: Reversal Strategy and Kinetics - C. James Watson; Michael D. Simpson; James D. Whitledge; Al Patterson; Michele M. Burns (Journal of Medical Toxicology, 2022)

Reimagining Sustainable Community Sports Fields of the Future: a Framework for Convergent Science-Stakeholder Decision-Making - C. M. Straw; B. P. McCullough; C. Segars; B. Daher; M. S. Patterson (Circular Economy and Sustainability, 2022)

Impact of Age, Sex, and Genetic Diversity in Murine Models of the Hematopoietic Acute Radiation Syndrome (H-ARS) and the Delayed Effects of Acute Radiation Exposure (DEARE) - Christie M. Orschell; Tong Wu; Andrea M. Patterson (Current Stem Cell Reports, 2022)

Ontogenetic shift in diet of a large elapid snake is facilitated by allometric change in skull morphology - M. Patterson; A. K. Wolfe; P. A. Fleming; P. W. Bateman; M. L. Martin; E. Sherratt; N. M. Warburton (Evolutionary Ecology, 2022)
As snakes are limbless, gape-limited predators, their skull is the main feeding structure involved in prey handling, manipulation and feeding. Ontogenetic changes in prey type and size are likely to be associated with distinct morphological changes in the skull during growth. We investigated ontogenetic variation in diet from stomach contents of 161 Dugite specimens ( Pseudonaja affinis , Elapidae) representing the full range of body size for the species, and skull morphology of 46 specimens (range 0.25–1.64 m snout-vent-length; SVL). We hypothesised that changes in prey type throughout postnatal ontogeny would coincide with distinct changes in skull shape. Dugites demonstrate a distinct size-related shift in diet: the smallest individuals ate autotomised reptile tails and reptiles, medium-sized individuals predominantly ate mammals, and the largest individuals had the most diverse diet, including large reptiles. Morphometric analysis revealed that ~40% of the variation in skull shape was associated with body size (SVL). Through ontogeny, skulls changed from a smooth, bulbous cranium with relatively small trophic bones (upper and lower jaws and their attachments), to more rugose bones (as a likely reflection of muscle attachment) and relatively longer trophic bones that would extend gape. Individual shape variation in trophic bone dimensions was greater in larger adults and this likely reflects natural plasticity of individuals feeding on different prey sizes/types. Rather than a distinct morphological shift with diet, the ontogenetic changes were gradual, but positive allometry of individual trophic bones resulted in disproportionate growth of the skull, reflected in increased gape size and mobility of jaw bones in adults to aid the ingestion of larger prey and improve manipulation and processing ability. These results indicate that allometric scaling is an important mechanism by which snakes can change their dietary niche.

A spatial and temporal assessment of nonresponse in the national forest inventory of the U.S - James A. Westfall; Todd A. Schroeder; Joseph M. McCollum; Paul L. Patterson (Environmental Monitoring and Assessment, 2022)

Impact of Post-Tropical Storm Arthur (2014) on benthic Arcellinida assemblage dynamics in Harvey Lake, New Brunswick, Canada - Dan Atasiei; Nawaf A. Nasser; Calder W. Patterson; Anqi Wen; R. Timothy Patterson; Jennifer M. Galloway; Helen M. Roe (Hydrobiologia, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Compound urban crises - Linda Westman; James Patterson; Rachel Macrorie; Christopher J. Orr; Catherine M. Ashcraft; Vanesa Castán Broto; Dana Dolan; Mukesh Gupta; Jeroen van der Heijden; Thomas Hickmann; Robert Hobbins; Marielle Papin; et al. (Ambio, 2022)
The crises that cities face—such as climate change, pandemics, economic downturn, and racism—are tightly interlinked and cannot be addressed in isolation. This paper addresses compound urban crises as a unique type of problem, in which discrete solutions that tackle each crisis independently are insufficient. Few scholarly debates address compound urban crises and there is, to date, a lack of interdisciplinary insights to inform urban governance responses. Combining ideas from complex adaptive systems and critical urban studies, we develop a set of boundary concepts (unsettlement, unevenness, and unbounding) to understand the complexities of compound urban crises from an interdisciplinary perspective. We employ these concepts to set a research agenda on compound urban crises, highlighting multiple interconnections between urban politics and global dynamics. We conclude by suggesting how these entry points provide a theoretical anchor to develop practical insights to inform and reform urban governance.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Upregulation of SIRT1 Contributes to dmPGE2-dependent Radioprotection of Hematopoietic Stem Cells - Liqiong Liu; Hongge Li; Andrea M. Patterson; P. Artur Plett; Carol H. Sampson; Khalid S. Mohammad; Maegan L. Capitano; Pratibha Singh; Chonghua Yao; Christie M. Orschell; Louis M. Pelus (Stem Cell Reviews and Reports, 2022)

A portable extruder for accurate and precise high-resolution subsampling of unconsolidated sediment cores - R. Timothy Patterson; Nawaf A. Nasser; Steven Tremblay; Jennifer M. Galloway (Journal of Paleolimnology, 2022)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Meloxicam with Filgrastim may Reduce Oxidative Stress in Hematopoietic Progenitor Cells during Mobilization of Autologous Peripheral Blood Stem Cells in Patients with Multiple Myeloma - Andrea M. Patterson; Shuhong Zhang; Liqiong Liu; Hongge Li; Pratibha Singh; Yunlong Liu; Sherif S. Farag; Louis M. Pelus (Stem Cell Reviews and Reports, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Prostaglandin E2 Enhances Aged Hematopoietic Stem Cell Function - Andrea M. Patterson; P. Artur Plett; Carol H. Sampson; Edward Simpson; Yunlong Liu; Louis M. Pelus; Christie M. Orschell (Stem Cell Reviews and Reports, 2021)

Correction to: Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Repeated ex situ Spawning in Two Highly Disease Susceptible Corals in the Family Meandrinidae - Keri L. O’Neil; Rachel M. Serafin; Joshua T. Patterson; Jamie R. K. Craggs (Frontiers in Marine Science, 2021)
Members of the family Meandrinidae are highly susceptible to stony coral tissue loss disease, resulting in population reductions up to 88% in both Dendrogyra cylindrus and Meandrina meandrites along the Florida Reef Tract. Reductions in abundance on this scale leave these species susceptible to limitations in sexual reproduction and natural recovery without intervention. In response to the ongoing outbreak of the disease across the Caribbean, a variety of genetic rescue projects have been implemented to bring disease susceptible species into ex situ culture and preserve living genetic diversity. In this study, corals being held in a long-term ex situ genetic bank were maintained using artificial lighting and temperature cues programmed to mimic natural cycles in Key Largo, FL, United States. Synchronized broadcast spawning events in both species were documented in aquaria over two annual spawning cycles in 2019 and 2020. Timing of gamete release relative to the perceived date and sunset was highly synchronized with wild observations. Up to 21 unique D. cylindrus genotypes collected from reef locations spanning over 230 km contributed gametes to the larval pool. The majority of these parental colonies are no longer alive in the wild. Repeatable and predictable ex situ spawning events such as these will become an essential tool for managed breeding and assisted fertilization in species suffering from severe population declines. These annual events have the potential to produce thousands of genetically diverse offspring for restoration efforts and offer future hope for the long-term survival of these threatened species.

Determining effective acoustic array design for monitoring presence of white sharks Carcharodon carcharias in nearshore habitats - Sofia M. Gabriel; T. A. Patterson; J. P. Eveson; J. M. Semmens; D. Harasti; P. A. Butcher; J. L. Y. Spaet; R. W. Bradford (Marine Biology, 2021)

Elevated Calf Mortality and Long-Term Responses of Wild Bottlenose Dolphins to Extreme Climate Events: Impacts of Foraging Specialization and Provisioning - Janet Mann; Vivienne Foroughirad; Molly H. F. McEntee; Madison L. Miketa; Taylor C. Evans; Caitlin Karniski; Ewa Krzyszczyk; Eric M. Patterson; John C. Strohman; Megan M. Wallen (Frontiers in Marine Science, 2021)
As demands for wildlife tourism increase, provisioning has become a popular means of providing up-close viewing to the public. At Monkey Mia, Shark Bay, Australia, up to five adult female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) visit a 100 m stretch of beach daily to receive fish handouts. In 2011, a severe marine heatwave (MHW) devastated seagrass and fish populations in Shark Bay. Offspring survival declined precipitously among seagrass specialists (dolphins that forage disproportionately in seagrass habitat). As all provisioned dolphins at the site are seagrass specialists, we examined how provisioned and non-provisioned seagrass specialists responded to the MHW. Using 27 years of data we compare habitat use, home range size, calf mortality, and predation risk between provisioned and non-provisioned females and their offspring before and after the MHW. Our results show that provisioned females have extremely small home ranges compared to non-provisioned females, a pattern attributable to their efforts to remain near the site of fish handouts. However, weaned offspring (juveniles) born to provisioned females who are not provisioned themselves also had much smaller home ranges, suggesting a persistent maternal effect on their behavior. After the MHW, adult females increased their use of seagrass habitats, but not their home range size. Provisioned females had significantly lower calf mortality than non-provisioned females, a pattern most evident pre-MHW, and, in the first 5 years after the MHW (peri-MHW, 2011–2015), calf mortality did not significantly increase for either group. However, the ecosystem did not recover, and post-MHW (2016–2020), calf mortality was substantially higher, regardless of provisioning status. With few survivors, the impact of the MHW on juvenile mortality post-weaning is not known. However, over three decades, juvenile mortality among offspring of provisioned vs. non-provisioned females did not statistically differ. Thus, the survival benefits accrued to calves in the provisioned group likely cease after weaning. Finally, although shark attack rates on seagrass specialists did not change over time, elevated predation on calves cannot be ruled out as a cause of death post-MHW. We discuss our results as they relate to anthropogenic influences on dolphin behavioral plasticity and responses to extreme climate events.

Climate effects on size‐at‐age and growth rate of Chinook Salmon ( Oncorhynchus tshawytscha ) in the Fraser River, Canada - Yi Xu; A. Scott Decker; Charles K. Parken; Lynda M. Ritchie; David A. Patterson; Caihong Fu (Fisheries Oceanography, 2020)
Decline in size‐at‐age of Chinook Salmon ( Oncorhynchus tshawytscha ) has been observed for many populations across the entire Northeast Pacific Ocean, and identifying external drivers of this decline is important for sustainable management of these ecologically, economically, and culturally valuable resources. We assessed size‐at‐age of 96,939 Chinook Salmon sampled in the Fraser River watershed (Canada) from 1969 to 2017. A broad decline in size‐at‐age was confirmed across all population aggregates of Fraser River Chinook Salmon, in particular since year 2000. By developing a novel probability‐based approach to calculate age‐ and year‐specific growth rates for Fraser River Chinook Salmon and relating growth rates to environmental conditions in specific years through a machine learning method (boosted regression trees), we were able to disentangle multi‐year effects on size‐at‐age and thus identify environmental factors that were most related to the observed size‐at‐age of Chinook Salmon. Among 10 selected environmental variables, ocean salinity at Entrance Island in spring, the Aleutian Low Pressure Index and the North Pacific Current Bifurcation Index were consistently identified as important contributors for four of the seven age and population aggregate combinations. These top environmental contributors could be incorporated into future stock assessment and forecast models to improve Chinook Salmon fisheries management under climate change.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Microplastics in Salt of Tuticorin, Southeast Coast of India - M. Narmatha Sathish; Immaculate Jeyasanta; Jamila Patterson (Archives of Environmental Contamination and Toxicology, 2020)

Changing Biogeochemistry and Invertebrate Community Composition at Newly Deployed Artificial Reefs in the Northeast Gulf of Mexico - Kendra K. Babcock; Florian Cesbron; William F. Patterson; Steven B. Garner; Lisa A. Waidner; Jane M. Caffrey (Estuaries and Coasts, 2020)

Selective Regulation of 5-HT1B Serotonin Receptor Expression in the Striatum by Dopamine Depletion and Repeated L-DOPA Treatment: Relationship to L-DOPA-Induced Dyskinesias - Fernando E. Padovan-Neto; Santanna Patterson; Nivea M. F. Voelkner; Feras Altwal; Joel A. Beverley; Anthony R. West; Heinz Steiner (Molecular Neurobiology, 2020)

Photography as a tool for avian morphometric measurements - Heather M. Williams; Samantha B. Wilcox; Andrea J. Patterson (Journal of Ornithology, 2020)

Multilocus phylogeny of a cryptic radiation of Afrotropical long‐fingered bats (Chiroptera, Miniopteridae) - Terrence C. Demos; Paul W. Webala; Holly L. Lutz; Julian C. Kerbis Peterhans; Steven M. Goodman; Natalia Cortés‐Delgado; Michael Bartonjo; Bruce D. Patterson (Zoologica Scripta, 2020)
The Old World bat family Miniopteridae comprises only the genus Miniopterus , which includes 20 currently recognized species from the Afrotropical realm and 15 species from Eurasia and Australasia. Since 2003, the number of recognized Miniopterus species has grown from 19 to 35, with most newly described species endemic to Madagascar and the Comoros Archipelago. We investigated genetic variation, phylogenetic relationships and clade membership in Miniopterus focusing on Afrotropical taxa. We generated mitochondrial cytochrome‐ b (cyt‐ b ) and nuclear intron data (five genes) from 352 vouchered individuals collected at 78 georeferenced localities. Including 99 additional mitochondrial sequences from GenBank, we analysed a total of 25 recognized species. Mitochondrial genetic distances among cyt‐ b ‐supported clades averaged 9.3%, representing as many as five undescribed species. Multilocus coalescent delimitation strongly supported the genetic isolation of eight of nine tested unnamed clades. A large number of sampled clades in sub‐Saharan Africa are distributed wholly or partly in East Africa (nine of 13 clades), suggesting that Miniopterus diversity has been grossly underestimated. Although 25 of 27 cyt‐ b and 23 of 25 nuclear gene tree lineages from the Afrotropics were strongly supported as monophyletic, a majority of deep nodes were poorly resolved in phylogenetic analyses. Long terminal branches subtending short backbone internodes in the phylogenetic analyses suggest a rapid radiation model of diversification. This hypothesis needs to be tested using more phylogenetically informative data.

NASA’s satellite laser ranging systems for the twenty-first century - J. F. McGarry; E. D. Hoffman; J. J. Degnan; J. W. Cheek; C. B. Clarke; I. F. Diegel; H. L. Donovan; J. E. Horvath; M. Marzouk; A. R. Nelson; D. S. Patterson; R. L. Ricklefs; et al. (Journal of Geodesy, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Movement responses to environment: fast inference of variation among southern elephant seals with a mixed effects model - I. D. Jonsen; C. R. McMahon; T. A. Patterson; M. Auger‐Méthé; R. Harcourt; M. A. Hindell; S. Bestley (Ecology, 2019)
Like many species, movement patterns of southern elephant seals ( Mirounga leonina ) are being influenced by long‐term environmental change. These seals migrate up to 4,000 km from their breeding colonies, foraging for months in a variety of Southern Ocean habitats. Understanding how movement patterns vary with environmental features and how these relationships differ among individuals employing different foraging strategies can provide insight into foraging performance at a population level. We apply new fast‐estimation tools to fit mixed effects within a random walk movement model, rapidly inferring among‐individual variability in southern elephant seal environment–movement relationships. We found that seals making foraging trips to the sea ice on or near the Antarctic continental shelf consistently reduced speed and directionality (move persistence) with increasing sea‐ice coverage but had variable responses to chlorophyll a concentration, whereas seals foraging in the open ocean reduced move persistence in regions where circumpolar deep water shoaled. Given future climate scenarios, open‐ocean foragers may encounter more productive habitat but sea‐ice foragers may see reduced habitat availability. Our approach is scalable to large telemetry data sets and allows flexible combinations of mixed effects to be evaluated via model selection, thereby illuminating the ecological context of animal movements that underlie habitat usage.

Eastern water dragons use alternative social tactics at different local densities - Kasha Strickland; Eric M Patterson; Céline H Frère (Behavioral Ecology and Sociobiology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

The reliability of pigment pattern‐based identification of wild bottlenose dolphins - Lena Marie Vetters Bichell; Ewa Krzyszczyk; Eric M Patterson; Janet Mann (Marine Mammal Science, 2018)
Long‐term studies often rely on natural markings for individual identification across time. The primary method for identification in small cetaceans relies on dorsal fin shape, scars, and other natural markings. However, dorsal fin markings can vary substantially over time and the dorsal fin can become unrecognizable after an encounter with a boat or shark. Although dorsal fins have the advantage in that they always break the water surface when the cetacean breathes, other physical features, such as body scars and pigmentation patterns can supplement. The goal of this study was to explore the use of dorso‐lateral pigment patterns to identify wild bottlenose dolphins. We employed photographic pigment matching tests to determine if pigmentation patterns showed (1) longitudinal consistency and (2) bilateral symmetry using a 30 yr photographic database of bottlenose dolphins ( Tursiops aduncus ). We compared experienced dolphin researchers and inexperienced undergraduate student subjects in their ability to accurately match images. Both experienced and inexperienced subjects correctly matched dolphin individuals at a rate significantly above chance, even though they only had 10 s to make the match. These results demonstrate that pigment patterns can be used to reliably identify individual wild bottlenose dolphins, and likely other small cetacean species at other sites.

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

A survey of microparasites present in adult migrating Chinook salmon ( Oncorhynchus tshawytscha ) in south‐western British Columbia determined by high‐throughput quantitative polymerase chain reaction - A L Bass; S G Hinch; A K Teffer; D A Patterson; K M Miller (Journal of Fish Diseases, 2017)
Microparasites play an important role in the demography, ecology and evolution of Pacific salmonids. As salmon stocks continue to decline and the impacts of global climate change on fish populations become apparent, a greater understanding of microparasites in wild salmon populations is warranted. We used high‐throughput, quantitative PCR (HT‐qRT‐PCR) to rapidly screen 82 adult Chinook salmon from five geographically or genetically distinct groups (mostly returning to tributaries of the Fraser River) for 45 microparasite taxa. We detected 20 microparasite species, four of which have not previously been documented in Chinook salmon, and four of which have not been previously detected in any salmonids in the Fraser River. Comparisons of microparasite load to blood plasma variables revealed some positive associations between Flavobacterium psychrophilum , Cryptobia salmositica and Ceratonova shasta and physiological indices suggestive of morbidity. We include a comparison of our findings for each microparasite taxa with previous knowledge of its distribution in British Columbia.

Sequential sample reservoirs for Itrax-XRF analysis of discrete samples - Braden R. B. Gregory; Eduard G. Reinhardt; Andrew L. Macumber; Nawaf A. Nasser; R. Timothy Patterson; Shawn E. Kovacs; Jennifer M. Galloway (Journal of Paleolimnology, 2017)

Mesophotic Coral Ecosystems: A Geoacoustically Derived Proxy for Habitat and Relative Diversity for the Leeward Shelf of Bonaire, Dutch Caribbean - Arthur C. Trembanis; Alexander L. Forrest; Bryan M. Keller; Mark R. Patterson (Frontiers in Marine Science, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

Shrinking of Vann Island, Gulf of Mannar, SE coast of India: assessing the impacts - M. Jayaprakash; K. Sivakumar; S. Muthusamy; R. R. Krishnamurthy; J. K. Edward Patterson (Natural Hazards, 2016)

Does maternal captivity of wild, migratory sockeye salmon influence offspring performance? - N. M. Sopinka; C. T. Middleton; D. A. Patterson; S. G. Hinch (Hydrobiologia, 2016)

Effects of experimentally elevated egg cortisol on offspring traits in two species of wild Pacific salmon - Natalie M. Sopinka; Scott G. Hinch; Stephen J. Healy; Graham D. Raby; David A. Patterson (Environmental Biology of Fishes, 2016)

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

First record of coralline lethal orange disease (CLOD) in the Indian Ocean - G. S. Aeby; K. Diraviya Raj; G. Mathews; M. Selva Bharath; J. K. Patterson Edward (Coral Reefs, 2015)

Benzotriazoles in the Aquatic Environment: a Review of Their Occurrence, Toxicity, Degradation and Analysis - M. D. Alotaibi; A. J. McKinley; B. M. Patterson; A. Y. Reeder (Water, Air, & Soil Pollution, 2015)

A comparison of survey and focal follow methods for estimating individual activity budgets of cetaceans - Caitlin Karniski; Eric M. Patterson; Ewa Krzyszczyk; Vivienne Foroughirad; Margaret A. Stanton; Janet Mann (Marine Mammal Science, 2015)
Activity budget data are essential for determining behavioral responses to physiological and ecological variables. Yet, few studies are available to investigate the robustness, accuracy, and biases of the methods used to estimate activity budgets for cetaceans. In this study, we compare activity budgets of 55 adult female bottlenose dolphins in Shark Bay, Australia derived from two methods: surveys ( n = 6,903) and focal follows ( n = 1,185, totaling 2,721 h of observation). Activity budgets estimated from survey data differed in all behavioral states compared to focal follow data. However, when controlling for temporal autocorrelation, only time spent socializing and time spent traveling remained disparate between the methods. To control for biases associated with assigning group‐level behavior to individuals, we also compared survey and focal follow activity budgets for lone females. Here we found differences between methods in time spent foraging and traveling regardless of whether we controlled for temporal autocorrelation, which suggests detection biases likely play a role in explaining differences in activity budget estimates between the two methodologies. Our results suggest that surveys are less representative of individual‐level activity budgets, and thus, when individual‐level knowledge about behavior is needed, focal follows are preferred.

Superresolution imaging of viral protein trafficking - Anamaris M. Colberg-Poley; George H. Patterson; Kyle Salka; Shivaprasad Bhuvanendran; David Yang; Jyoti K. Jaiswal (Medical Microbiology and Immunology, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada - Lindsay M. Upiter; Jesse C. Vermaire; R. Timothy Patterson; Carley A. Crann; Jennifer M. Galloway; Andrew L. Macumber; Lisa A. Neville; Graeme T. Swindles; Hendrik Falck; Helen M. Roe; Michael F. J. Pisaric (Journal of Paleolimnology, 2014)

Mother knows best, even when stressed? Effects of maternal exposure to a stressor on offspring performance at different life stages in a wild semelparous fish - N. M. Sopinka; S. G. Hinch; C. T. Middleton; J. A. Hills; D. A. Patterson (Oecologia, 2014)

Discussions and decisions of the 2012–2014 International Committee on Taxonomy of Viruses (ICTV) Filoviridae Study Group, January 2012–June 2013 - Alexander A. Bukreyev; Kartik Chandran; Olga Dolnik; John M. Dye; Hideki Ebihara; Eric M. Leroy; Elke Mühlberger; Sergey V. Netesov; Jean L. Patterson; Janusz T. Paweska; Erica Ollmann Saphire; Sophie J. Smither; et al. (Archives of Virology, 2014)

Eating frequency and risk of colorectal cancer - Martine M. Perrigue; Elizabeth D. Kantor; Theresa A. Hastert; Ruth Patterson; John D. Potter; Marian L. Neuhouser; Emily White (Cancer Causes & Control, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Using PET / CT imaging to characterize 18 F‐fluorodeoxyglucose utilization in fish - Z S Browning; A A Wilkes; D S MacKenzie; R M Patterson; M W Lenox (Journal of Fish Diseases, 2013)
Fish are becoming an increasingly important research species as investigators seek alternatives to mammalian models. Combined positron emission tomography/computed tomography with 18 F‐fluorodeoxyglucose ( FDG ‐ PET / CT ) is a powerful new technology that has been extensively applied for high‐resolution imaging in mammals but not fish. CT scanning provides detailed anatomical three‐dimensional imaging. PET scanning detects areas of cellular activity using radio‐labelled molecular probes with specific uptake rates appropriate to the tissue involved. FDG ‐ PET is used in oncology because tissues with high glucose uptake, such as neoplasms, are intensely radio‐labelled. PET / CT combines the two technologies, so that images acquired from both devices are merged into one superimposed image, thus more precisely correlating metabolic activity with anatomical three‐dimensional imaging. Our objective was to determine if fish can be viable replacement animals in cancer studies using this technique by analysing the similarities between fish and humans in glucose uptake in select organs across multiple fish species. Rapid, quantifiable glucose uptake was demonstrated, particularly in brain, kidneys and liver in all imaged fish species. Standard uptake values for glucose uptake in the major organ systems of fish were more similar to those of humans than mice or dogs, indicating that fish may serve as effective alternative animal models using this technology. Applications for this technique in fish may include oncogenesis and metabolism studies as well as screening for environmental carcinogenesis.

Does among‐population variation in burst swimming performance of sockeye salmon Oncorhynchus nerka fry reflect early life migrations? - N. M. Sopinka; S. G. Hinch; A. G. Lotto; C. K. Whitney; D. A. Patterson (Journal of Fish Biology, 2013)
Using a fixed‐speed test, burst swimming performance was found to vary among nine populations of emergent sockeye salmon Oncorhynchus nerka fry reared in a common‐garden environment. No consistent relationship was, however, detected between difficulty of fry migration (upstream v . downstream) to rearing areas and total burst swimming duration or bursting rate.

Prostate specific membrane antigen produces pro-angiogenic laminin peptides downstream of matrix metalloprotease-2 - Rebecca E. Conway; Kyle Joiner; Alex Patterson; David Bourgeois; Robert Rampp; Benjamin C. Hannah; Samantha McReynolds; John M. Elder; Hannah Gilfilen; Linda H. Shapiro (Angiogenesis, 2013)

Diggin′ on U(biquitin): A Novel Method for the Identification of Physiological E3 Ubiquitin Ligase Substrates - Carrie E. Rubel; Jonathan C. Schisler; Eric D. Hamlett; Robert M. DeKroon; Mathias Gautel; Oscar Alzate; Cam Patterson (Cell Biochemistry and Biophysics, 2013)

Genetic perspectives on “Lion Conservation Units” in Eastern and Southern Africa - J. M. Dubach; M. B. Briggs; P. A. White; B. A. Ament; B. D. Patterson (Conservation Genetics, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Conserving large carnivores: dollars and fence - C. Packer; A. Loveridge; S. Canney; T. Caro; S.T. Garnett; M. Pfeifer; K.K. Zander; A. Swanson; D. MacNulty; G. Balme; H. Bauer; C.M. Begg; et al. (Ecology Letters, 2013)
Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced reserves can maintain lions at 80% of their potential densities on annual management budgets of $500 km −2 , unfenced populations require budgets in excess of $2000 km −2 to attain half their potential densities. Lions in fenced reserves are primarily limited by density dependence, but lions in unfenced reserves are highly sensitive to human population densities in surrounding communities, and unfenced populations are frequently subjected to density‐independent factors. Nearly half the unfenced lion populations may decline to near extinction over the next 20–40 years.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

The physiological consequences of catch‐and‐release angling: perspectives on experimental design, interpretation, extrapolation and relevance to stakeholders - S. J. Cooke; M. R. Donaldson; C. M. O'connor; G. D. Raby; R. Arlinghaus; A. J. Danylchuk; K. C. Hanson; S. G. Hinch; T. D. Clark; D. A. Patterson; C. D. Suski (Fisheries Management and Ecology, 2013)
Over the past 20 years, there has been a dramatic increase in the use of physiological tools and experimental approaches for the study of the biological consequences of catch‐and‐release angling practices for fishes. Beyond simply documenting problems, physiological data are also being used to test and refine different strategies for handling fish such that stress is minimised and survival probability maximised, and in some cases, even for assessing and facilitating recovery post‐release. The inherent sensitivity of physiological processes means that nearly every study conducted has found some level of – unavoidable – physiological disturbance arising from recreational capture and subsequent release. An underlying tenet of catch‐and‐release studies that incorporate physiological tools is that a link exists between physiological status and fitness. In reality, finding such relationships has been elusive, with further extensions of individual‐level impacts to fish populations even more dubious. A focus of this article is to describe some of the challenges related to experimental design and interpretation that arise when using physiological tools for the study of the biological consequences of catch‐and‐release angling. Means of overcoming these challenges and the extrapolation of physiological data from individuals to the population level are discussed. The argument is presented that even if it is difficult to demonstrate strong links to mortality or other fitness measures, let alone population‐level impacts of catch‐and‐release, there remains merit in using physiological tools as objective indicators of fish welfare, which is an increasing concern in recreational fisheries. The overarching objective of this paper is to provide a balanced critique of the use of physiological approaches in catch‐and‐release science and of their role in providing meaningful information for anglers and managers.

Paleoenvironmental reconstruction of the Early to Middle Miocene Central Paratethys using stable isotopes from bryozoan skeletons - Marcus M. Key; Kamil Zágoršek; William P. Patterson (International Journal of Earth Sciences, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Vertebrate metacommunity structure along an extensive elevational gradient in the tropics: a comparison of bats, rodents and birds - Steven J. Presley; Laura M. Cisneros; Bruce D. Patterson; Michael R. Willig (Global Ecology and Biogeography, 2012)
Aim We evaluated the structure of metacommunities for each of three vertebrate orders (Chiroptera, Rodentia and Passeriformes) along an extensive elevational gradient. Using elevation as a proxy for variation in abiotic characteristics and the known elevational distributions of habitat types, we assessed the extent to which variation in those factors may structure each metacommunity based on taxon‐specific characteristics. Location Manu Biosphere Reserve in the Peruvian Andes. Methods Metacommunity structure is an emergent property of a set of species distributions across geographic or environmental gradients. We analysed elements of metacommunity structure (coherence, range turnover and range boundary clumping) to determine the best‐fit structure for each metacommunity along an elevational gradient comprising 13 250‐m elevational intervals and 58 species of rodent, 92 species of bat or 586 species of passerine. Results For each taxon, the environmental gradient along which the metacommunity was structured was highly correlated with elevation. Clementsian structure (i.e. groups of species replacing other such groups along the gradient) characterized rodents, with a group of species that was characteristic of rain forests and a group of species that was characteristic of higher elevation habitats (i.e. above 1500 m). Distributions of bats were strongly nested, with more montane communities comprising subsets of species at lower elevations. The structure of the passerine metacommunity was complex and most consistent with a quasi‐Clementsian structure. Main conclusions Each metacommunity exhibited a different structure along the same elevational gradient, and each structure can be accounted for by taxon‐specific responses to local environmental factors that vary predictably with elevation. The structures of rodent and bird metacommunities suggest species sorting associated with habitat specializations, whereas structure of the bat metacommunity is probably moulded by a combination of species‐specific tolerances to increasingly cold, low‐productivity environs of higher elevations and the diversity and abundance of food resources associated with particular habitat types.

Observations on saliva osmolality during progressive dehydration and partial rehydration - Nigel A. S. Taylor; Anne M. J. van den Heuvel; Pete Kerry; Sheena McGhee; Gregory E. Peoples; Marc A. Brown; Mark J. Patterson (European Journal of Applied Physiology, 2012)

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

An Investigation into the Utility of a Multi-compartmental, Dynamic, System of the Upper Gastrointestinal Tract to Support Formulation Development and Establish Bioequivalence of Poorly Soluble Drugs - Paul A. Dickinson; Ragheb Abu Rmaileh; Lee Ashworth; Richard A. Barker; Wendy M. Burke; Claire M. Patterson; Nick Stainforth; Mohammed Yasin (The AAPS Journal, 2012)

The complimentary role of genetic and ecological data in understanding population structure: a case study using moose (Alces alces) - L. A. Finnegan; P. J. Wilson; G. N. Price; S. J. Lowe; B. R. Patterson; M.-J. Fortin; D. L. Murray (European Journal of Wildlife Research, 2012)

Non-steroidal anti-inflammatory drugs and cancer incidence by sex in the VITamins And Lifestyle (VITAL) cohort - Theodore M. Brasky; John D. Potter; Alan R. Kristal; Ruth E. Patterson; Ulrike Peters; Maryam M. Asgari; Mark D. Thornquist; Emily White (Cancer Causes & Control, 2012)

Parental identity influences progeny responses to incubation thermal stress in sockeye salmon Onchorhynchus nerka - J. M. Burt; S. G. Hinch; D. A. Patterson (Journal of Fish Biology, 2012)
The influence of individual parentage on progeny responses to early developmental temperature stress was examined in a cross‐fertilization experiment using sockeye salmon Oncorhynchus nerka . Differences in survival, hatch timing and size were examined among five paternally linked and five maternally linked offspring families (Weaver Creek population, British Columbia, Canada) incubated at 12, 14 and 16° C from just after fertilization to hatch. Mean embryonic survival was significantly lower at 14 and 16° C; however, offspring families had substantially different survival responses across the thermal gradient (crossing reaction norms). Within temperature treatments, substantial variation in embryonic survival, alevin mass, time‐to‐hatch and hatch duration were attributable to family identity; however, most traits were governed by significant temperature–family interactions. For embryonic survival, large differences between families at 16° C were due to both female and male spawner influence, whereas inter‐family differences were obscured at 14° C (high intra‐family variation), and minimal at 12° C (only maternal influence detected). Despite post‐hatch rearing under a common cool thermal regime, persistent effects of both temperature and parentage were detected in alevin and 3 week‐old fry. Collectively, these findings highlight the crucial role that parental influences on offspring may have in shaping future selection within salmonid populations exposed to elevated thermal regimes. An increased understanding of parental and temperature influences and their persistence in early development will be essential to developing a more comprehensive view of population spawning success and determining the adaptive capacity of O. nerka populations in the face of environmental change.

Physiological and molecular endocrine changes in maturing wild sockeye salmon, Oncorhynchus nerka, during ocean and river migration - A.-M. Flores; J. M. Shrimpton; D. A. Patterson; J. A. Hills; S. J. Cooke; T. Yada; S. Moriyama; S. G. Hinch; A. P. Farrell (Journal of Comparative Physiology B, 2012)

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

The importance of parentage in assessing temperature effects on fish early life history: a review of the experimental literature - J. M. Burt; S. G. Hinch; D. A. Patterson (Reviews in Fish Biology and Fisheries, 2011)

The After Breast Cancer Pooling Project: rationale, methodology, and breast cancer survivor characteristics - Sarah J. Nechuta; Bette J. Caan; Wendy Y. Chen; Shirley W. Flatt; Wei Lu; Ruth E. Patterson; Elizabeth M. Poole; Marilyn L. Kwan; Zhi Chen; Erin Weltzien; John P. Pierce; Xiao Ou Shu (Cancer Causes & Control, 2011)

Effect of MDM2 and vascular endothelial growth factor inhibition on tumor angiogenesis and metastasis in neuroblastoma - Danielle M. Patterson; Dongbing Gao; Denae N. Trahan; Brett A. Johnson; Andrew Ludwig; Eveline Barbieri; Zaowen Chen; Jose Diaz-Miron; Lyubomir Vassilev; Jason M. Shohet; Eugene S. Kim (Angiogenesis, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

Selenium in surface and irrigation water in the Kendrick irrigation district, Wyoming - Michelle M. Patterson; Ginger B. Paige; Katta J. Reddy (Environmental Monitoring and Assessment, 2010)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A Holocene record of Pacific Decadal Oscillation (PDO)-related hydrologic variability in Southern California (Lake Elsinore, CA) - M. E. Kirby; S. P. Lund; W. P. Patterson; M. A. Anderson; B. W. Bird; L. Ivanovici; P. Monarrez; S. Nielsen (Journal of Paleolimnology, 2010)

Infection of gill and kidney of Fraser River sockeye salmon, Oncorhynchus nerka (Walbaum), by Parvicapsula minibicornis and its effect on host physiology - M J Bradford; J Lovy; D A Patterson (Journal of Fish Diseases, 2010)
Adult sockeye salmon, Oncorhynchus nerka (Walbaum), migrating upstream in the Fraser River, British Columbia, are exposed to the myxozoan parasite Parvicapsula minibicornis when they enter the river from the ocean. Infections are initially localized in the kidney but have recently been associated with branchitis in one population. Adult fish from five locations in the watershed were sampled to determine whether branchitis was widespread. P. minibicornis infections in kidney glomeruli were prevalent in all samples except for a sample of fish that had just entered the Fraser River from the ocean. For fish captured in spawning streams, parasites were observed in the renal tubules and gill, and branchitis was observed in 70% of fish. Plasma osmolality was negatively correlated with the number of parasites in the kidney tubules, which we hypothesize to be caused by the breach of glomerular membranes as the parasite leaves the fish. Plasma lactate values increased with increasing levels of pathology in gills. These findings support the hypothesis that P. minibicornis impacts the physiology of migrating fish, which may in turn affect the likelihood that adults will be able to migrate and spawn successfully.

A new high-latitude record for the macaroni penguin (Eudyptes chrysolophus) at Avian Island, Antarctica - K. B. Gorman; E. S. Erdmann; B. C. Pickering; P. J. Horne; J. R. Blum; H. M. Lucas; D. L. Patterson-Fraser; W. R. Fraser (Polar Biology, 2010)

Controls on the contemporary distribution of lake thecamoebians (testate amoebae) within the Greater Toronto Area and their potential as water quality indicators - Helen M. Roe; R. Timothy Patterson; Graeme T. Swindles (Journal of Paleolimnology, 2010)

Larval supply is a good predictor of recruitment in endemic but not non-endemic fish populations at a high latitude coral reef - A. J. Crean; S. E. Swearer; H. M. Patterson (Coral Reefs, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Effects of an Oil Spill on the Regrowth of Emergent Vegetation in a Northern Alberta Lake - Barbara G. Wernick; Adrian M. H. deBruyn; Luanne Patterson; Peter M. Chapman (Archives of Environmental Contamination and Toxicology, 2009)

Toward a Rational Exuberance for Ecosystem Services Markets - Jeffrey D. Kline; Marisa J. Mazzotta; Trista M. Patterson (Journal of Forestry, 2009)
Ecosystem services markets have become a popular topic among environmental policymakers and ecosystem protection advocates. Their proponents view markets as a promising new way to finance conservation of threatened ecosystems worldwide at a time when the need for additional protection seems especially critical. Their advocates in forestry promise that such markets will soon offer new financial opportunities to forest landowners to augment or even replace income from the sale of timber, thereby increasing financial incentives for landowners to retain land in forests. But what is the real promise in ecosystem services markets and what can realistically be achieved by their implementation? We provide an overview of how environmental markets work in theory and discuss several issues that influence how effective they can be. We conclude that the promise of ecosystem services markets greatly depends on the particular circumstances of program implementation, including what services are to be traded and whether they are amenable to trading, the ability to enact and enforce regulation sufficient to induce trading, and how expected program results compare with those likely to arise from other conservation policy approaches.

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Origin of yellowtail kingfish, Seriola lalandi , from Lord Howe Island, Australia, inferred from otolith chemistry - Heather M. Patterson; Stephen E. Swearer (New Zealand Journal of Marine and Freshwater Research, 2008)
Yellowtail kingfish, Seriola lalandi (Family Carangidae), sustain important commercial and recreational fisheries in New South Wales (NSW), Australia. However, little is known about their population structure, particularly whether the kingfish around Lord Howe Island (LHI) comprise a distinct stock, separate from that of the NSW stock. We examined the otolith chemistry from juvenile kingfish collected from LHI, several NSW sites and Elizabeth and Middleton reefs (EMR) and compared those elemental signatures to the juvenile portion of adult otoliths collected from LHI to determine where the adults may have originated. Our results indicate a robust separation in otolith signatures from different locations (error rate of classification ranged from 3.5% to 9.9%), and suggest that a significant proportion of the adult kingfish sampled (28%) may have originated in the waters around LHI or nearby EMR. Further research may indicate that the management of kingfish in NSW waters could benefit from a more spatially explicit strategy.

Cold shock and fish - M. R. Donaldson; S. J. Cooke; D. A. Patterson; J. S. Macdonald (Journal of Fish Biology, 2008)
Rapid decreases in water temperature may result in a number of physiological, behavioural and fitness consequences for fishes termed ‘cold shock’. Cold‐shock stress occurs when a fish has been acclimated to a specific water temperature or range of temperatures and is subsequently exposed to a rapid decrease in temperature, resulting in a cascade of physiological and behavioural responses and, in some cases, death. Rapid temperature decreases may occur from either natural ( e.g. thermocline temperature variation, seiches and storm events) or anthropogenic sources ( e.g. varied thermal effluents from power generation and production industries). The magnitude, duration and frequency of the temperature change as well as the initial acclimation temperatures of individuals can influence the extent of the consequences of cold shock on fishes. Early research on cold shock focused on documenting mortality events associated with cold shock. However, in recent years, a shift in research has occurred where the focus of cold‐shock studies now involves characterizing the sublethal effects of cold shock in terms of the stress response in fishes. This shift has revealed that cold shock can actually be used as a tool for fisheries science ( e.g. to induce polyploidy). The cold‐shock stress response offers opportunities to develop many exciting research questions, yet to date, cold‐shock research has been largely unfocused. Few studies attempt to link laboratory physiology experiments with ecologically relevant field data on behaviour, growth, bioenergetics and fitness. Additional research will allow for the development of more focused and robust management policies and conservation initiatives. This review synthesizes the sublethal physiological and behavioural consequences of cold‐shock stress on fishes, identifies natural and anthropogenic sources of cold shock, discusses the benefits of cold shock to fisheries science and describes mitigation and management efforts. Existing knowledge gaps and opportunities for future cold‐shock research are presented.

Phylogeny of the Rodent Genus Isothrix (Hystricognathi, Echimyidae) and its Diversification in Amazonia and the Eastern Andes - Bruce D. Patterson; Paúl M. Velazco (Journal of Mammalian Evolution, 2008)

Effects of diluted Kraft pulp mill effluent on hybrid poplar and soil chemical properties - S. J. Patterson; D. S. Chanasyk; E. Mapfumo; M. A. Naeth (Irrigation Science, 2008)

Ecosystem Services and Emergent Vulnerability in Managed Ecosystems: A Geospatial Decision-Support Tool - Colin M. Beier; Trista M. Patterson; F. Stuart Chapin (Ecosystems, 2008)

Diatoms and pollen as indicators of water quality and land-use change: a case study from the Oak Ridges Moraine, Southern Ontario, Canada - Melissa A. Watchorn; Paul B. Hamilton; Thane W. Anderson; Helen M. Roe; R. Timothy Patterson (Journal of Paleolimnology, 2008)

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

Impact of the 2005 coral bleaching event on Porites porites and Colpophyllia natans at Tektite Reef, US Virgin Islands - K. R. T. Whelan; J. Miller; O. Sanchez; M. Patterson (Coral Reefs, 2007)

The complete genome sequence for an American isolate of enterovirus 77 - M. S. Oberste; K. Maher; M. A. Patterson; M. A. Pallansch (Archives of Virology, 2007)

Use of sonar transects to improve efficiency and reduce potential bias in visual surveys of reef fishes - Heather M. Patterson; Malcolm Lindsay; Stephen E. Swearer (Environmental Biology of Fishes, 2007)

Paleoecological Assessment of Watershed History in PRIMENet Watersheds at Acadia National Park, USA - M. Schauffler; S. J. Nelson; J. S. Kahl; G. L. Jacobson; T. A. Haines; W. A. Patterson; K. B. Johnson (Environmental Monitoring and Assessment, 2007)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Long-term Evaluation of a Composite Cover Overlaying a Sulfidic Tailings Facility - B. M. Patterson; B. S. Robertson; R. J. Woodbury; B. Talbot; G. B. Davis (Mine Water and the Environment, 2006)

Elemental signatures of Acanthochromis polyacanthus otoliths from the Great Barrier Reef have significant temporal, spatial, and between-brood variation - Heather M. Patterson; Michael J. Kingsford (Coral Reefs, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Impact of Soil Amendments on Broccoli Quality and Napropamide Movement Under Field Conditions - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2005)

Resolution of the early life history of a reef fish using otolith chemistry - Heather M. Patterson; Michael J. Kingsford; Malcolm T. McCulloch (Coral Reefs, 2005)

A paleolimnological record of Holocene climate and environmental change in the Temagami region, northeastern Ontario - Robert E. A. Boudreau; Jennifer M. Galloway; R. Timothy Patterson; Arun Kumar; Frederick A. Michel (Journal of Paleolimnology, 2005)

Orexin inputs to caudal raphé neurons involved in thermal, cardiovascular, and gastrointestinal regulation - Hans-Rudolf Berthoud; Laurel M. Patterson; Gregory M. Sutton; Christopher Morrison; Huiyuan Zheng (Histochemistry and Cell Biology, 2005)

Molecular genetic variation across the southern and eastern geographic ranges of the African lion, Panthera leo - Jean Dubach; B. D. Patterson; M. B. Briggs; K. Venzke; J. Flamand; P. Stander; L. Scheepers; R. W. Kays (Conservation Genetics, 2005)

Brain mitochondrial injury in human immunodeficiency virus–seropositive (HIV+) individuals taking nucleoside reverse transcriptase inhibitors - Brian C Schweinsburg; Michael J Taylor; Omar M Alhassoon; Raul Gonzalez; Gregory G Brown; Ronald J Ellis; Scott Letendre; John S Videen; J Allen McCutchan; Thomas L Patterson; Igor Grant; the HNRC Group (Journal of NeuroVirology, 2005)

Model-Based Inference of Recombination Hotspots in a Highly Variable Oncogene - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

Cold-water acclimation does not modify whole-body fluid regulation during subsequent cold-water immersion - J. M. Stocks; M. J. Patterson; D. E. Hyde; A. B. Jenkins; K. D. Mittleman; N. A. S. Taylor (European Journal of Applied Physiology, 2004)

Population structure of red drum ( Sciaenops ocellatus ) as determined by otolith chemistry - H. M. Patterson; N. Julien; R. S. McBride (Marine Biology, 2004)

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Recombination Does Not Occur in Newly Identified Diverged Oceanic Picornaviruses - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

Model-Based Inference of Recombination Hotspots in a Highly, Variable Oncogene - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

VARIABILITY IN THE DIET OF HARBOR PORPOISES ( PHOCOENA PHOCOENA ) IN SCOTTISH WATERS 1992–2003 - M. B. Santos; G. J. Pierce; J. A. Learmonth; R. J. Reid; H. M. Ross; I. A. P. Patterson; D. G. Reid; D. Beare (Marine Mammal Science, 2004)
A bstract Interannual, seasonal, and regional variation in the diet of porpoises, Phocoena phocoena , in Scottish (UK) waters was studied using stomach contents of animals stranded between 1992 and 2003. Most samples came from the east coast (including many porpoises killed by bottlenose dolphins), with smaller numbers from the west coast and from Shetland. The most important prey types, in terms of contribution by number and mass, were whiting ( Merlangius merlangus ) and sand eels (Ammodytidae). Multivariate analysis confirmed the existence of regional, seasonal, and interannual variation in diet, as well as differences ( i. e. , biases) related to cause of death. These differences were further explored using univariate analyses. Sand eels were more important in the summer months (quarters 2 and 3) and on the east coast, whereas gadids were more important in winter and in the Shetland area. Some, but not all, observed trends in the numerical importance and size of prey taken were consistent with trends in abundance and size of fish taken during research trawl surveys. There was some evidence that porpoises Clupea harengus and sprat Sprattus sprattus ) formed a relatively small proportion of the diet, but their importance varied from year to year. Although possible methodological biases prevent firm conclusions, it appears that the importance of clupeids in porpoise diet may have decreased since the 1960s, mirroring the decline in North Sea herring abundance. The recovery of the North Sea herring stock in recent years is not as yet reflected in porpoise diet.

Toward estimation of map accuracy without a probability test sample - Brian M. Steele; David A. Patterson; Roland L. Redmond (Environmental and Ecological Statistics, 2003)

Pesticide Residues in Soil and Quality of Potato Grown with Sewage Sludge - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2003)

Letters - C.P. Patterson; B. Daniels; N.R. Bosic; J. Coufal; M. Stevens (Journal of Forestry, 2003)

Vanilloid receptor (VR1) expression in vagal afferent neurons innervating the gastrointestinal tract - Laurel M. Patterson; Huiyuan Zheng; Sean M. Ward; Hans-Rudolf Berthoud (Cell and Tissue Research, 2003)

Expression Profile of the Channel Catfish Spleen: Analysis of Genes Involved in Immune Functions - Arif M. Kocabas; Ping Li; Dongfeng Cao; Attila Karsi; Chongbo He; Andrea Patterson; Zhenlin Ju; Rex A. Dunham; Zhanjiang Liu (Marine Biotechnology, 2002)

Post-Younger Dryas climate interval linked to circumpolar vortex variability: isotopic evidence from Fayetteville Green Lake, New York - Kirby M.; Patterson W.; Mullins H.; Burnett A. (Climate Dynamics, 2002)

Non-traditional study designs to demonstrate average bioequivalence for highly variable drug products - Scott D. Patterson; Névine M.-D. Zariffa; Timothy H. Montague; Kate Howland (European Journal of Clinical Pharmacology, 2001)

Seasonal variation in stable oxygen and carbon isotope values recovered from modern lacustrine freshwater mollusks: paleoclimatological implications for sub-weekly temperature records - Christopher M. Wurster; William P. Patterson (Journal of Paleolimnology, 2001)

Immunohistochemical identification of cholecystokinin A receptors on interstitial cells of Cajal, smooth muscle, and enteric neurons in rat pylorus - Laurel M. Patterson; Huiyuan Zheng; Sean M. Ward; Hans-Rudolf Berthoud (Cell and Tissue Research, 2001)

A geochemical survey of spring water from the main Ethiopian rift valley, southern Ethiopia: implications for well-head protection - Jeffrey M. McKenzie; Donald I. Siegel; William Patterson; D. Jonathan McKenzie (Hydrogeology Journal, 2001)

Angiotensin II induces gene transcription through cell-type-dependent effects on the nuclear factor-κB (NF-κB) transcription factor - Allan R. Brasier; M. Jamaluddin; Youqui Han; Cam Patterson; Marschall S. Runge (Molecular and Cellular Biochemistry, 2000)

Taking varves to bits: Scanning electron microscopy in the study of laminated sediments and varves - Jean M. Dean; Alan E.S. Kemp; David Bull; Jennifer Pike; Gunilla Patterson; Bernd Zolitschka (Journal of Paleolimnology, 1999)

Anchoring of canine linkage groups with chromosome-specific markers - Petra Werner; Cathryn S. Mellersh; Michael G. Raducha; Susan DeRose; Gregory M. Acland; Ulana Prociuk; Neil Wiegand; Gustavo D. Aguirre; Paula S. Henthorn; Donald F. Patterson; Elaine A. Ostrander (Mammalian Genome, 1999)

Analysis of otolith chemistry in Nassau grouper ( Epinephelus striatus ) from the Bahamas and Belize using solution-based ICP-MS - H. M. Patterson; S. R. Thorrold; J.M. Shenker (Coral Reefs, 1999)

Substrate use during and following moderate- and low-intensity exercise: Implications for weight control - D. L. Thompson; K. M. Townsend; R. Boughey; K. Patterson; D. R. Bassett Jr (European Journal of Applied Physiology, 1998)

A comparative analysis of nested subset patterns of species composition - David H. Wright; Bruce D. Patterson; Greg M. Mikkelson; Alan Cutler; Wirt Atmar (Oecologia, 1997)

Vitamin supplements and cancer risk: the epidemiologic evidence - R. E. Patterson; E. White; A. R. Kristal; M. L. Neuhouser; J. D. Potter (Cancer Causes & Control, 1997)

Simulation of the effect of methane bubble plumes on vertical mixing in Mono Lake - Jos R. Romero; John C. Patterson; John M. Melack (Aquatic Sciences, 1996)

Location and geometric description of carpal bones in CT images - H. D. Tagare; K. W. Elder; D. M. Stoner; R. M. Patterson; C. L. Nicodemus; S. F. Viegas; G. R. Hillman (Annals of Biomedical Engineering, 1993)

Biological effects of tolytoxin (6-hydroxy-7-O-methyl-scytophycin b), a potent bioactive metabolite from cyanobacteria - Gregory M. L. Patterson; Shmuel Carmeli (Archives of Microbiology, 1992)

Applications of immunogold labelling in animal and plant virology - S. Patterson; B. J. M. Verduin (Archives of Virology, 1987)

Modulation of lectin-stimulated lymphocyte agglutination and mitogenesis by estrogen metabolites: effects on early events of lymphocyte activation - Richard W. Pfeifer; Rachel M. Patterson (Archives of Toxicology, 1986)

Mouse hepatitis virus strain 3 infection of C57, A/Sn and A/J strain mice and their macrophages - M. R. Macnaughton; S. Patterson (Archives of Virology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Sectional notes - Louis Soffcke; Julian C. Miller; Frank W. Hussey; E. L. Newdick; T. M. Patterson; Robert Schmidt; D. M. James (American Journal of Potato Research, 1937)